Bering: Time series analysis for Bering Sea climate data (R software package) - Knudson, Christina P. (UST Research Online, 2018)
Using Monte Carlo and Markov chain Monte Carlo, this package conducts hypothesis tests for the time-series climate data presented by Karla Knudson, Christina Ravelo, Ivano Aiello, Christina Knudson, Michelle Drake, and Tatsuhiko Sakamoto. (v. 1.0)